Penokohan dan Ambisi Karakter King dalam Anime One Punch Man Karya One - Ansiska, Paisal; Paradida, Yulia Putri; Tarigan, Marsten Lihardo (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2024)
Anime One Punch Man is a literary work realized in the form of animation (anime). Anime is an art form created in the animation format, typically produced in Japan and characterized by the unique Japanese animation style. One of the characters in the anime One Punch Man is King, who is an S-class hero known for being very strong and respected. This research aims to uncover the ambitions of the character King in the anime series One Punch Man by One. The study takes the form of describing and understanding the characters in the anime. This research utilizes qualitative descriptive research methods. The purpose of using qualitative analysis methods in the analysis of One Punch Man characters is to gain a detailed and comprehensive understanding of the characters in the anime. The results of this research show that the character King has a large physical appearance, yellow hair, wears armor, and has three vertical scar marks on the left side of his face. King does not have grand ambitions to become a powerful hero. King's ambition is simply to strive so that the truth that he doesn't possess any superpowers remains unknown to many.